Fast as a gazelle – young firms gaining from educational diversity - Eklund, Carita; van Criekingen, Kristof (Taylor and Francis, 2022)
Young, high-growth firms, so-called gazelles, are an important source of growth and industry dynamics. However, our understanding is lacking on how knowledge competences support high growth among young firms. This article aims to fill this gap by utilising firm and employee knowledge stocks, and diversity in educational backgrounds. The firm’s stock of knowledge capital is measured by intangible capital that is calculated from organisational, product development and ICT investments. The employees’ knowledge stock is approximated by their completed educational degrees. Our data originate from Danish registers and covers 2000–2016. The findings indicate that intangible capital has the potential to increase the likelihood of becoming a gazelle. We further find that educational diversity is beneficial but is moderated by firms’ knowledge intensity.
Keywords: High education; gazelle; intangible capital; high growth; fast growth; employment; knowledge competences; fi=Taloustiede|en=Economics|